(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
In the developed (open) market economy enterprises are the subjectsof multiple trade transactions. It becomes more and more important toassess an enterprise’s value in both aspects – macroeconomic – tradetransactions and microeconomic as well – which is essential to evaluatecurrent, but first of all the future shape and activities of the company.In the traditional approach an enterprise’s value is built up by theamount of material assets and their ability to generate future incomesestimated as cash flows. However most of the companies build theireconomic power even though the dependency on own possession islimited. The standard of the value in many cases determinates also theselection of evaluation methods as well as it points the factors to be putinto analysis and perspectives of the branch, enterprise’s strategicanalysis. In the paper there has been put special attention to analysis ofinterior of the enterprise and its environment. There has been made theestimation of the enterprise’s value with the use of liquidation method.There has been estimated the costs and incomes predicted for years2006-2010 with production shrinking assumption. There has beenverified theoretical premises together with empirical analysis whatconfirmed the urge to select the methods on individual basis